Ask a New Question
Search
Look at the steps for solving the equation and choose
Explain how solving a linear inequality is similar to solving a linear equation.
Choose the correct answer below. • A. The
1 answer
120 views
Look at the steps for solving the equation and choose a true statement.
3х - 9х + 1 = 2 (-3x + 1) - 1 6х +1 = -6x + 2 -1 -6x +
1 answer
53 views
Look at the steps for solving the equation and choose a true statement.
3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
1 answer
asked by
HELP
285 views
Look at the steps for solving the equation and choose a true statement.
3x - 9x + 1 = 2(- 3x + 1) - 1 - 6x + 1 = - 6x + 2 - 1 -
1 answer
82 views
Look at the steps for solving the equation and choose a true statement.
3x - 9x + 1 = 2(-3x + 1) - 1 -6x + 1 = -6x + 2 - 1 -6x +
2 answers
asked by
????
236 views
Look at the steps for solving the equation and choose a true statement.
3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
1 answer
101 views
Question 6 (1 point)
Look at the steps for solving the equation and choose a true statement. 10 + 6x = 15 + 9x - 3x 10 + 6x = 15
1 answer
123 views
Look at the steps for solving the equation and choose a true statement.
3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
9 answers
84 views
Look at the steps for solving the equation and choose a true statement. ◂=▸◂−▸3x−9x+1=2◂()▸(−3x+1)−1
1 answer
36 views
Look at the steps for solving the equation and choose a true statement.
3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
1 answer
38 views